COVID-19 Age-Mortality Curves Are Flatter in Developing Countries - Demombynes, Gabriel (World Bank, Washington, DC, 2020)
A greater share of reported COVID-19 deaths occur at younger ages in low- and middle-income countries (LMICs) compared to high-income countries (HICs). Based on data from 26 countries, people age 70 and older constitute 37 percent of deaths attributed to COVID-19 in LMICs on average, versus 87 percent in HICs. Only part of this difference is accounted for by differences in population age structure. In this paper, COVID-19 mortality rates are calculated for each age group by dividing the number of COVID-19 deaths by the underlying population. The resulting age-mortality curves are flatter in countries with lower incomes. In HICs, the COVID-19 mortality rate for those ages 70-79 is 12.6 times the rate for those ages 50-59. In LMICs, that ratio is just 3.5. With each year of age, the age-specific mortality rate increases by an average of 12.6 percent in HICs versus 7.1 percent in LMICs. This pattern holds overall and separately for men's and women's mortality rates. It reflects some combination of variation across countries in age patterns of infection rates, fatality rates among those infected, and under-attribution of deaths to COVID-19. The findings highlight that experiences with COVID-19 in wealthy countries may not be generalizable to developing countries.